Interferon-β-related tumefactive brain lesion in a Caucasian patient with neuromyelitis optica and clinical stabilization with tocilizumab - Harmel, Jens; Jarius, Sven (BMC neurology, 2014)
Background: Neuromyelitis optica (NMO) is a severely disabling inflammatory disorder of the central nervous system and is often misdiagnosed as multiple sclerosis (MS). There is increasing evidence that treatment options shown to be beneficial in MS, including interferon-β (IFN-β), are detrimental in NMO. Case presentation: We here report the first Caucasian patient with aquaporin 4 (AQP4) antibody (NMO-IgG)-seropositive NMO presenting with a tumefactive brain lesion on treatment with IFN-β. Disease started with relapsing optic neuritis and an episode of longitudinally extensive transverse myelitis (LETM) in the absence of any brain MRI lesions or cerebrospinal fluid-restricted oligoclonal bands. After initial misdiagnosis of multiple sclerosis (MS) the patient received subcutaneous IFN-β1b and, subsequently, subcutaneous IFN-β1a therapy for several years. Under this treatment, the patient showed persisting relapse activity and finally presented with a severe episode of subacute aphasia and right-sided hemiparesis due to a large T2 hyperintensive tumefactive lesion of the left brain hemisphere and a smaller T2 lesion on the right side. Despite rituximab therapy two further LETM episodes occurred, resulting in severe neurological deficits. Therapeutic blockade of the interleukin (IL)-6 signalling pathway by tocilizumab was initiated, followed by clinical and radiological stabilization. Conclusion: Our case (i) illustrates the relevance of correctly distinguishing NMO and MS since these disorders differ markedly in their responsiveness to immunomodulatory and -suppressive therapies; (ii) confirms and extends a previous report describing the development of tumefactive brain lesions under IFN-β therapy in two Asian NMO patients; and (iii) suggests tocilizumab as a promising therapeutic alternative in highly active NMO disease courses.
Gesehen am 20.10.2020